Perilaku Pencarian Informasi Mahasiswa Sastra Inggris Universitas Diponegoro dalam Menyelesaikan Tugas Perkuliahan - Farah Hindun Istiqomah; Yanuar Yoga Prasetyawan (Pustabiblia: Journal of Library and Information Science, 2022)
This study aimed to find out how information seeking behavior of English Literature major students from Diponegoro University using internet to completing their college assignments. This study used qualitative method and purposive sampling in selecting informants with semi-structured interview as a data collection. The interview conducted on 12 undergraduate students from Diponegoro University’s English Literature major. This study used thematic analysis in analyzing the data. The results of this study show that undergraduate students from Diponegoro University’s English Literature major need information that can help them completing their college assignments which can be found by conducting information seeking activities. Information seeking activities carried out by these students used internet with sources such as search engine Google, scientific journals sites, downloadable literary works sites, sites that provide information related to literary works, movie streaming apps and social media. Information seeking activities are carried out by determining the sources, seeking information, selecting information, evaluating information, checking the credibility of information, monitoring the development of information and applying it to their college assignments. The problem that students experienced while doing information seeking activities is a certain kinds of information that are difficult to find.